FY2015-FY2017 Medium-Term Budget. (Policy Papers; Policy Paper, 2014)
The proposed FY 15-17 Medium-Term Budget (MTB) was formulated within the Fund's strategic planning framework to align allocation of resources to the delivery of institutional priorities.